Meta-Analysis: Effects of Exposure to Tobacco Smoke and Malnutrition on the Risk of Pneumonia in Children - Minawati, Atika Dwi; Murti, Bhisma; Prasetya, Hanung (Journal of Epidemiology and Public Health, 2023)
Background: Exposure to tobacco smoke (ETS) and poor nutritional status affect the risk of pneumonia in children. The purpose of this study was to analyze and estimate the effect of exposure to tobacco smoke and nutritional status in children on the risk of pneumonia. Subjects and Method: The meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: children under five. Intervention: exposure to tobacco smoke and poor nutritional status. Comparison: no exposure to tobacco smoke and no malnutrition status. Outcome: Pneumonia. The online databases used are Google Scholar, PubMed, and Scient Direct with the keywords “Pneumonia” AND “Exposure to tobacco smoke” AND “Poor nutritional status” AND “Children under five years” AND “Multivariate” AND “Cross-sectional”. The inclusion criteria were full-text, cross-sectional study, and published in English. The data were analyzed by RevMan 5.3. Results: A meta-analysis included 14 cross-sectional studies from Hong Kong, Nepal, Mongolia, Morocco, Uganda, Cameroon, Ethiopia, Nigeria, Egypt, and China. The total sample was 52,863 children under five. The results of the meta-analysis showed that exposure to tobacco smoke was 2.08 times more at risk of developing pneumonia than children under five who were not exposed (aOR=2.08; Cl 95%=1.30 to 3.32; p= 0.002). The presence of poor nutritional status is 2.00 times more at risk of experiencing pneumonia than children under five with no malnutrition status. (aOR=2.00; 95% Cl=1.31 to 3.06; p= 0.001). Conclusion: Exposure to tobacco smoke and poor nutritional status in toddlers can increase the risk of pneumonia. Keywords: exposure to tobacco smoke, poor nutritional status, children under five years pneumonia. Correspondence:Atika Dwi Minawati. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: dwiminawatiatika@gmail.com. Mobile: +625212613303.